Effect of Clay Mineral Content and Confining Pressure on Energy Dissipation Characteristics of Basalt with Different Overburden Depths. (17th May 2022) - Chen, Yan; Zhou, Lei; Wang, Gaofei; Bai, Erhu; Guo, Baohua
Abstract : With the deepening of coal mining in China, dynamic disasters occur with the release of energy. In this study, in order to study the difference between shallow rock and deep rock, conventional triaxial compression tests were carried out on basalts with different overburden depths. The mechanical properties and energy evolution characteristics of basalts with different overburden depths were analyzed. The results show that the strength parameters increase with increasing depths, while the deformation parameters exhibit the opposite phenomenon. The strength and peak strain of basalt with the same depth increase with increasing confining pressure. However, the elastic modulus almost remains unchanged. The prepeak total input energy and dissipation energy decrease with increasing depths, and total elastic energy increases with increasing depths which indicates that the deep rock releases more energy than shallow rock when failure occurs. The input energy, elastic energy, and dissipation energy increase with increasing confining pressure. However, elastic energy ratio decreases with increasing confining pressure. The strength parameters and elastic energy increase with increasing density and deformation parameter, while the dissipation energy decreases. This phenomenon has the opposite law when clay mineral content is increased. The conclusions of this study may provide theoretical reference to dynamic disasters induced by energy in deep coal mines.